Pullback attractor for the three dimensional nonautonomous primitive equations of large‐scale ocean and atmosphere dynamics. Issue 2 (7th November 2019) - You, Bo
Abstract : The main objective of this paper is concerned with the existence of a finite fractal dimensional pullback attractor for the three‐dimensional nonautonomous primitive equations of large‐scale ocean and atmosphere dynamics. Under some slightly strong assumptions on the heat source, we prove the existence of a pullback attractor in a more regular phase space by asymptotical a priori estimates and provide the upper bound of the fractal dimension of the pullback attractor in V by calculating the Lyapunov exponent.